Corporate social responsibility: a study of premium luxury hotels on the Balearic Islands - Miguel Trías-Vilar; María Antonia García-Sastre (Responsibility and Sustainability, 2013)
This paper deals with the subject of Corporate Social Responsibility as a key element to design internal marketing strategies and changes related to the luxury hotel industry on the Balearic Islands. Although all changes are still fresh in the manager’s mind, something seems to be changing in the internal managerial tourism performance according to recent studies.